S51. The ischemic test on anconeus muscle in myasthenia gravis. (May 2018) - Troni, Walter; Bianco, Chiara; Sapio, Alessia Di; Mongini, Tiziana
Abstract : Introduction: Classic techniques of repetitive stimulation still deserve to be exploited as the first diagnostic approach in disorders of neuromuscular transmission for the relative technical simplicity, rapid execution and higher specificity. Activation procedures, in particular muscle fatigue to prolonged repetitive stimulation under ischemia, have long been proposed to increase the diagnostic yield of repetitive stimulation. Of course, the procedure has so far been used in the less sensitive distal muscles, making its possible effectiveness largely counteracted by the unfavourable site of application. Kennett and Fawcett (1993) demonstrated that repetitive stimulation of anconeus muscle was more sensitive than abductor digiti minimi but equally sensitive as deltoid. Since the anatomical location of anconeus allows application of an inflated cuff proximally to it, we applied the fatigue-ischemic test on this muscle to take advantage of a possible synergetic effect of an effective activation procedure applied on a sensitive district. Methods: Since the fatigue-ischemic test has never been applied before on anconeus, a preliminary study was performed in 12 normal volunteers to define the specific duration of the fatigue-ischemia period, suitable to fully exhaust neuro-muscular transmission without inducing false positive results. We examined 27 patients with defined myasthenia (I: 8, IIa: 9, IIIa: 5, IIb: 1, IIIb: 3, IVb:1); on clinical examination, most of them showed a satisfactory clinical control; all of them were examined under therapy. Results: Preliminary evaluation in normal subjects demonstrated that the usual duration of fatigue under ischemia employed in distal muscles (4–6 min), induced in anconeus false positive results during repetitive trains in almost all normal controls. After having tested several activation periods of progressively shorter duration, the safe procedure resulted to be no more than 2.5 min of 5 Hz repetitive stimulation under ischemia, followed, maintaining ischemia, by 4 trains of 8 stimuli at 3 Hz, delivered every 30 s. Basal repetitive stimulation was abnormal in 13 p. (48%); 5 more patients (18.5%) resulted positive only after the activation procedure. In only 4 patients (14.8%) the basal test was positive in abductor digiti minimi. The procedure was well tolerated in all patients, mainly due to of the short duration of ischemia Conclusion: The short duration of fatigue under ischemia adequate to fully exhaust neuro-muscular transmission in anconeus proves that basal safety margin of neuromuscular transmission is significantly lower in this muscle than in hand muscles; this well explains the greater sensitivity of anconeus to repetitive stimulation in myasthenic patients. The ischemic test provided an increase of the diagnostic yield of about 30%. This result is relevant as it was obtained in a casuistry of myasthenic patients under therapy with acceptable clinical control.